THE INFLUENCE OF ONLINE MARKETING STRATEGY ON MSME SALES IN MEDAN CITY DURING PANDEMY COVID-19 - Muhammad Zuardi (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The spread of the Covid 19 virus has an impact on decreasing turnover of entrepreneurs, including small entrepreneurs who partner with online applications. An online marketing strategy is needed that can increase sales volume during a pandemic. This study aims to recommend the right marketing strategy to increase sales. Selling is an integrated effort to develop strategic plans aimed at satisfying the needs and desires of buyers, in order to get sales that generate profits. The results showed that the online marketing strategy did not significantly increase the sales of MSMEs in Medan City during the Covid-19 Pandemic. 10.5% of MSME sales in Medan City During the Covid-19 Pandemic can be explained or influenced by the Online Marketing Strategy, while the rest is explained or influenced by other variables